The Effect of Copper Nanoparticle Extract of Myrtus communis and Nerium oleander Plants on Biofilm Formation in Staphylococcus aureus - Dhaidan, Basheer M.; Majeed, Majid R. (Iraqi Journal of Science, 2025)
This study examined the fnbA gene, which plays a role in biofilm formation, in Staphylococcus aureus bacteria that were exposed to copper nanoparticles (CuNPs) produced using an aqueous extract from the leaves of Myrtus communis and Nerium oleander plants. A total of 54 S. aureus bacteria were isolated from wastewater samples. Gene expression analysis was conducted using a quantitative RT-PCR readyMix apparatus with a classical conventional PCR model of BIOER – Germany. The cDNA samples from S. aureus bacteria and fnbA gene were quantified using quantitative real-time PCR by applying SYBR green using a two-step RT-PCR method to determine the effect of CuNPs on biofilm formation gene. Characterization of CuNPs was performed using UV-light Visible spectroscopy, Atomic Force Microscope (AFM), and X-ray diffractometer (XRD). The obtained results of gene expression level in S. aureus isolates showed an increase in the level of expression of fnbA genes of bacteria isolates subjected to the CuNPs biosynthesized using M. communis, N. oleander aqueous extracts in addition to the mix of CuNPs, where the mean fnbA level of control bacteria were 26.525. In contrast, the mean level was increased significantly to 34.0, 34.15, and 35.025 for CuNPs biosynthesized using M. communis, N. oleander, and CuNPs mix respectively. In summary, all extracts effected on gene expression of fnbA gene but the mix extract of CuNPs had the highest effect.